A novel design of underground distribution cable fault locator system. Issue 1 (2nd January 2022) - Mandake, Yogesh B.; Holmukhe, R. M.; Gandhar, Abhishek
Abstract: Underground cables/wires find numerous applications in today's world in transmission, distribution, and industrial/commercial premises. Although underground system is having more benefits, it creates many problems once fault occurs. This paper includes discussion on current scenario of fault locating techniques. Paper presents innovative technique to detect open circuit and short circuit fault in underground cable or wire. Prototype developed and tested for practical readings. Conclusion drawn from obtained test results and includes discussed suggestions for further work in the same area.